Application of Gamma Ray-Dose on Two Varieties of Sugar Palm to Obtain The Best Growth Rate - Siswanda, Najmah Khalidah; Andi Apriany Fatmawaty; Widia Eka Putri; Abdul Hasyim Sodiq (Jurnal Agroekoteknologi Terapan, 2025)
The sugar palm (Arenga pinnata Merr.) is one of the palm species in Indonesia which offers numerous benefits. However, its slow growth until reaching a productive stage has contributed to a decline in its overall productivity over time. Gamma-ray irradiation has emerged as a potential approach to improve the genetic quality in order to enhance its productivity. The aim of this study is to determine the optimal growth rate resulting from various doses of gamma-ray irradiation and two sugar palm varieties. The research employed a factorial Randomized Group Design (RGD). The first factor was the dose of gamma-ray radiation (B) which consisted of five levels: 0 Gy (control), 4 Gy, 6 Gy, 8 Gy, and 10 Gy. The second factor was the sugar palm variety (V) which consisted of two levels: parasi sugar palm and Lebak local sugar palm. Each treatment was repeated three times, with each unit containing two plants, yielding a total of 60 seedlings. The result shows that the doses of gamma radiation 4 Gy provide the best effects on plant height, leaf width, and number of leaves. In addition, the greenish leaves provide the best effect on radiation dose of 6 Gy.